2021
DOI: 10.1007/s12672-021-00460-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of radiomics features at MRI in nasopharyngeal carcinoma

Abstract: Purpose To explore the value of MRI-based radiomics features in predicting risk in disease progression for nasopharyngeal carcinoma (NPC). Methods 199 patients confirmed with NPC were retrospectively included and then divided into training and validation set using a hold-out validation (159: 40). Discriminative radiomic features were selected with a Wilcoxon signed-rank test from tumors and normal masticatory muscles of 37 NPC patients. LASSO Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…I compared the predictive performance to previous studies on the same data. It was found that the AUC values of our model were higher in both the training and validation cohort ( S2 Fig ) [ 34 36 ], but these results contain more features and sequences. In our study, the CRM showed higher predictive performance than CM, in both the training and the validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…I compared the predictive performance to previous studies on the same data. It was found that the AUC values of our model were higher in both the training and validation cohort ( S2 Fig ) [ 34 36 ], but these results contain more features and sequences. In our study, the CRM showed higher predictive performance than CM, in both the training and the validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, radiomics labelling can be a useful supplement to clinical features in terms of prognostic value, which can explain the prognostic prediction performance of the radiomics model in the present study is better than that of the clinical model. The potential clinical value of predictive models based on radiomics in predicting PFS in NPC patients has been previously emphasized [ 21 , 34 ]. However, previous reports mostly used the Cox model to predict the prognosis of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports mostly used the Cox model to predict the prognosis of NPC. Different studies included different stages and treatment methods for NPC patients, resulting in different clinical and radiomics features, thereby increasing the study heterogeneity and affecting the prediction performance [ 21 23 ]. A study [ 35 ] constructed a Cox proportional hazard regression model to predict the PFS of NPC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation